Water and irrigation policy impact assessment using business simulation games: Evidence from northern Germany - Matthias Buchholz; Gesa Holst; Oliver Musshoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
To date, studies dealing with the impact assessment of changing irrigation policies predominately rely on normative rational choice models that are subject to rather restrictive assumptions such as profit-maximizing behavior. However, there is increasing evidence that decision makers pursue multiple goals and could be affected by bounded rationality, the extent of which is likely to vary amongst farmers. Against this background, we apply a business simulations game for the ex ante policy impact assessment of irrigation water policies that has the potential to reveal the 'true' behavior of the participants. To do so, we investigate how real farmers from the northeastern part of Lower Saxony respond to a water pricing scheme and a water quota intending to reduce water withdrawals for irrigation. In the business simulation game, the participants manage a 'virtual' cash crop farm for which they have to choose the crop allocation and irrigation applications during several production periods while facing uncertain product prices and weather conditions. The results from the business simulation game reveal that the applied water quota is more effective in reducing the amount of irrigation than the water pricing scheme. Moreover, we find that the participants' risk attitude affects the applied amount of irrigation in the business simulation game.
Keywords: 330; business simulation games; impact assessment; water quotas; water pricing schemes; irrigation; GAMLSS; zero-adjusted regression